2023
DOI: 10.1128/aem.00543-23
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Vibrio Blooms in the Xisha Islands May Associate with the 2020 Coral Bleaching Event

Abstract: Coral reefs exert important roles in maintaining the sustainability of marine ecosystems but decline worldwide due to various drivers, especially pathogenic microorganisms. Here, we investigated the distribution pattern and interactions of total bacteria and Vibrio spp. in the sediments from Xisha Islands during the coral bleaching event of 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In addition, coral bleaching occurred in the Xisha Islands in 2020 may be another reason for the high Vibrio abundance [ 32 ]. Bleached corals release twice as much particulate organic carbon (POC) and particulate nitrogen (PN) than normal corals [ 61 ], and coral pathogenic microbes may respond rapidly to these nutrient pulses [ 62 , 63 ]. It has been reported that vibrios usually can respond to fluctuations in nutrient concentrations and show a tendency of explosive reproduction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, coral bleaching occurred in the Xisha Islands in 2020 may be another reason for the high Vibrio abundance [ 32 ]. Bleached corals release twice as much particulate organic carbon (POC) and particulate nitrogen (PN) than normal corals [ 61 ], and coral pathogenic microbes may respond rapidly to these nutrient pulses [ 62 , 63 ]. It has been reported that vibrios usually can respond to fluctuations in nutrient concentrations and show a tendency of explosive reproduction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 d). The 2020 coral bleaching event in the Xisha Islands may cause the increasements of coral pathogenic vibrios [ 63 ]. With high coral number, Vibrio in the Xisha Islands may be developed as the dominant group by influencing coral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information of coral thermal bleaching percentage was obtained and reanalyzed from coral reef survey in the 15–20°N regions (Hainan Island, Xisha Island, and Zhongsha Islands) of SCS in the coral thermal bleaching event of 2020 ( 136 138 ). The data set of coral reef surveys of 2020 was constructed by line intercept transect techniques (atoll: 5–15 m; fringing reef: 2–6 m) and Point Intercept Transect video re-sampling ( 66 , 139 , 140 ) according to our benthic surveys and previous studies ( 137 , 140 , 141 ).…”
Section: Methodsmentioning
confidence: 99%
“…The dominant bacteria of different coral species are similar, which were distributed in Gammaproteobacteria , Alphaproteobacteria , Firmicutes [ 27 ], Bacteroidetes , and Actinobacteria . Coral bleaching may be attributed to the dominant Vibrio associated with corals [ 28 ]. In this study, seawater samples were collected near the coral reefs in the SCS, including Daya bay (DY), Qionghai (QH), Xisha islands (XS), and the Southern South China Sea (SSCS) during May to October 2020.…”
Section: Introductionmentioning
confidence: 99%